Deposition of superparamagnetic iron‐oxide nanoparticles in axillary sentinel lymph nodes following subcutaneous injection. Issue 3 (21st December 2012) - Johnson, Laura; Pinder, Sarah E; Douek, Michael
<x xml:space="preserve">Abstract</x> Aims Superparamagnetic iron oxide nanoparticle (SPIO)‐enhanced axillary lymph node magnetic resonance imaging (MRI) has the potential to supersede sentinel lymph node (SLN) biopsy in the management of early breast cancer with in vivo pre‐operative metastasis detection. We evaluated the distribution and extent of SPIOs within the SLN and its impact on routine histological assessment. Methods and results A total of 131 SLNs from 51 consecutive patients with breast cancer were examined histologically following subcutaneous injection of 2–4 ml SPIOs. SLNs were identified intra‐operatively using the combined technique. Ex vivo histological analysis was performed and the distribution of SPIOs assessed using standard haematoxylin and eosin staining. SPIO distribution was predominantly within lymph node sinuses (81%); fewer nodes contained iron in the subcapsular space (24%) and parenchyma (14%). In 58%, SPIOs were sequestered in macrophages. SPIOs were not seen within the areas of nodes containing metastases, but was seen surrounding the metastases. Conclusions Following subcutaneous injection of SPIOs, iron deposition is found predominantly in sinuses and the subcapsular space and is not found in areas containing metastases. This reinforces the notion that high resolution SPIO‐enhanced MRI has the potential for in vivo metastasis in the SLN in breast cancer. Routine histological examination was unaffected.